Evolving an Effective Legal Protection for Women’s Inheritance Rights in Ghana: A Need for Legal Reforms and Implementation - Yeboah-Appiah, Angela (Université d'Ottawa / University of Ottawa, 2023)
This thesis analyzes the inequality women face in the inheritance regime in Ghana. The existing legal framework which includes customary law is fraught with challenges that hinder women from claiming a fair share of their inheritance rights. Existing customary laws conflict with statutory law. Customary law contains aspects that contradict principles of equality espoused in statutory law. Additionally, the court relies on “judicial customary law” which contains old inheritance practices that do not reflect socio-economic changes. Finally, the judiciary in Ghana also uses the repugnancy doctrine in the interpretation and application of customary law. However, the repugnancy doctrine is outdated and constitutes a major hindrance for women in claiming a fair share of their inheritance rights. Drawing on postcolonial theory, intersectional feminism, law and society and sociology of law theories, this dissertation investigates and addresses the injustices associated with women’s rights of inheritance in Ghana. A major goal is to provide viable pathways that will ensure an equitable framework in the sharing of intestate property.
Keywords: inheritance rights; customary law; Women; succession